2015
DOI: 10.1590/1414-431x20154574
|View full text |Cite
|
Sign up to set email alerts
|

Decreased brain-derived neurotrophic factor plasma levels in psoriasis patients

Abstract: Brain-derived neurotrophic factor (BDNF) is associated with neuroplasticity and synaptic strength, and is decreased in conditions associated with chronic stress. Nevertheless, BDNF has not yet been investigated in psoriasis, a chronic inflammatory systemic disease that is exacerbated by stress. Therefore, our aim was to determine BDNF plasma levels in psoriasis patients and healthy controls. Adult patients (n=94) presenting with psoriasis for at least 1 year were enrolled, and age- and gender-matched with heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
5
22
2
1
Order By: Relevance
“…Furthermore, fluoxetine treatment produced an increase in BDNF and TrkB expression. Previous studies have shown that BDNF is decreased in patients with psoriasis, suggesting BDNF as a potential psoriasis biomarker . This is also consistent with our study, and we further confirmed this by showing that the TrkB antagonist K252a could reverse the effects of fluoxetine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, fluoxetine treatment produced an increase in BDNF and TrkB expression. Previous studies have shown that BDNF is decreased in patients with psoriasis, suggesting BDNF as a potential psoriasis biomarker . This is also consistent with our study, and we further confirmed this by showing that the TrkB antagonist K252a could reverse the effects of fluoxetine.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that BDNF is decreased in patients with psoriasis, suggesting BDNF as a potential psoriasis biomarker. 17 This is also consistent with our study, and we further confirmed this by showing that the TrkB antagonist K252a could reverse the effects of fluoxetine. We also confirmed that fluoxetine treatment is able to attenuate pathological lesions in K5.Stat3C mice.…”
Section: Discussionsupporting
confidence: 92%
“…We also did not detect the relationship between the levels of BDNF and NGF in the serum and skin samples and the PASI value in patient groups. Consistent with our results, Schulte-Herbrüggen et al (23) found no relationship between the serum NGF level and PASI values in psoriasis patients and Brunoni et al (21) found plasma BDNF levels to be similar in moderate and severe psoriasis cases.…”
Section: Discussionsupporting
confidence: 91%
“…Theoretically speaking, this is all assumed to be due to a mutation in the regulatory cytokine IL-10 or defects in surrounding regulatory T cells; however, the inflammatory pathway itself is not unique [29]. A neurotrophin known as brain-derived neurotrophic factor (BDNF), which plays an integral role in neuroplasticity and mental disorders, was found to be associated with psoriasis by Brunoni et al [34]. The authors calculated the blood BDNF levels instead of brain BDNF levels and found that these BDNF levels are reduced in depression and psoriasis.…”
Section: Immunological Changes In Psoriasismentioning
confidence: 99%